1983
DOI: 10.1071/ph830443b
|View full text |Cite
|
Sign up to set email alerts
|

New H2O Masers associated with Main-line OH Masers in the Galactic Longitude Range 3° to 60°

Abstract: A search in the direction of OH masers emitting at 1665 or 1667 MHz has yielded 11 new H 2 0 masers. The new sources are discussed individually. The overall statistics of the search show that out of a total of 55 OH masers in the 3° to 60° galactic longitude range at least 36 have H 2 0 maser counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…This source is an HC H ii region identified by Beltrán et al (2007), which is found to be associated with many CH 3 OH masers (Surcis et al 2015;Bartkiewicz et al 2016) and OH masers (Forster & Caswell 2000;Caswell et al 2013), H 2 O masers (Caswell et al 1983;Forster & Caswell 2000), and outflows traced by CO (Furuya et al 2002;Beltrán et al 2011) and SiO (Codella et al 2013). Its physical properties such as n e , diam, and EM (Table 8) are consistent with previous results (Beltrán et al 2007;Cesaroni et al 2019).…”
Section: G0247898+00833supporting
confidence: 87%
See 1 more Smart Citation
“…This source is an HC H ii region identified by Beltrán et al (2007), which is found to be associated with many CH 3 OH masers (Surcis et al 2015;Bartkiewicz et al 2016) and OH masers (Forster & Caswell 2000;Caswell et al 2013), H 2 O masers (Caswell et al 1983;Forster & Caswell 2000), and outflows traced by CO (Furuya et al 2002;Beltrán et al 2011) and SiO (Codella et al 2013). Its physical properties such as n e , diam, and EM (Table 8) are consistent with previous results (Beltrán et al 2007;Cesaroni et al 2019).…”
Section: G0247898+00833supporting
confidence: 87%
“…7). This source was found to host H 2 O masers (Caswell et al 1983), OH masers (Caswell et al 2013) and CH 3 OH masers (Bartkiewicz et al 2016), and is associated with CO outflows (Yang et al 2018), broad molecular lines such as SiO (2-1) (Csengeri et al 2016), N 2 H + , and HCO + (Shirley et al 2013) and millimeter RRLs (∆V = 40.34 km s −1 ; Kim et al 2017). The blue-shifted and red-shifted methanol masers spots mapped by Bartkiewicz et al (2016) have a similar orientation as the blue-shifted and red-shifted outflows mapped by Yang et al (2018).…”
Section: G0247898+00833mentioning
confidence: 98%
“…The OH 1665 MHz emission shows a similar morphology and velocity range (Argon et al 2000). Caswell (2001) reports the OH 6035 MHz emission and there may also be a water maser emission in the region (Caswell et al 1983). However, an uncertainty of the absolute position in declination is large and we are not able to verify the detailed association.…”
Section: Resultsmentioning
confidence: 74%
“…Kesteven 78 (G32.8-0.1), with a partly brightened radio shell, was identified as a Galactic SNR by Caswell et al (1975) based on the 408 and 5000MHz observations. A distance of ∼ 8 pc was estimated using the radio surface brightness -diameter (Σ-D) relationship (Caswell et al 1983). A 21cm HI observation with a resolution 2 ′ × 130 ′ × 6.3 km s −1 was made by Gosachinskii & Khersonskii (1985), which suggested a corresponding local standard of rest (LSR) velocity of 90 km s −1 , a distance of 9 kpc, and an age of 12 kyr for the SNR.…”
Section: Introductionmentioning
confidence: 99%